Analysis of Stakeholder Engagement in the Regional Water Supply System of Jatigede Project: A Study of Actor-Network Theory - Ilvan Prasetia Nugraha; Ayomi Dita Rarasati; Achmad Jaka Santos Adiwijaya (Journal of International Conference Proceedings (JICP), 2019)
Water is important things that must be provided to support the survival and economic improvement of a region. The rapid development in eastern West Java causes the need for water is increasing. The purpose of this paper is to identify stakeholders' involvement and the impact of changes in cooperation schemes in the project. This study uses a qualitative method with the Actor-Network Theory approach to explore stakeholders. The implementation of the Water Supply System project arose several problems, such as indications that the regional government wanted to change the Public-Private Partnership scheme to Business to Business. It has an impact on the lack of integration and coordination among stakeholders because there is no coordination management for the stakeholders involved.